Declines in an Augur Buzzard Buteo augur Population in a Region of Increasing Human Development - Eichenwald, Adam J.; Amar, Arjun; Tyrrell, Peter; Buechley, Evan R.; Virani, Munir Z. (Frontiers in Ecology and Evolution, 2021)
As with many areas in Africa, Kenya has witnessed rapid human development in recent decades, including an increase in urbanization and an intensification of agriculture. The impact of these land use changes on wildlife populations have, however, rarely been examined. The Augur Buzzard is a widespread raptor species, thought to adapt relatively well to human alterations of habitat. In this study, we explore trends in Augur Buzzard (Buteo auguralis) territory occupancy over nearly two decades around Lake Naivasha, Kenya, in relation to suspected land-use changes, particularly expansion in human housing and flower farms. We hypothesized that these changes would cause population declines in this species within our study area. Using remote-sensed satellite imagery, we found that human development (agriculture and human settlement) increased from 9% to 24% of the study area from 1995 to 2014. We found a 47% decline in active territories over this same time period, representing an annualized decline of 3.1%. Based on the length of three generations this would qualify this species to be uplisted to at least Vulnerable in our study area, raising our concerns that the same pattern may be occurring across the species’ range. We then explored whether abandonment of individual territories was associated with either i) the current amount or ii) the change in human development within a range of buffer circles of varying radii (0.1 km – 5.0 km). Contrary to our expectations, no associations were found between human development and territorial abandonment, and thus we could not attribute specific territorial abandonment to these broad scale anthropogenic land cover changes. We encourage further research to investigate whether territorial abandonment may be associated with either finer resolution (habitat specific) changes, or sources of direct mortality, for example human persecution or electrocutions. These factors might explain the decline in this population better than overall broader scale increases in anthropogenic land cover.